Beta-fluoroamphetamines via the stereoselective synthesis of benzylic fluorides. - Cresswell, A; Davies, S; Lee, J; Roberts, P; Russell, A; Thomson, J; Tyte, M (2010)
A range of substituted aryl epoxides undergo efficient ring-opening hydrofluorination upon treatment with 0.33 equiv of BF(3) x OEt(2) in CH(2)Cl(2) at -20 degrees C to give the corresponding syn-fluorohydrins, consistent with a mechanism involving a stereoselective S(N)1-type epoxide ring-opening process. The benzylic fluoride products of these reactions are valuable templates for further elaboration, as demonstrated by the preparation of a range of aryl-substituted beta-fluoroamphetamines.